After dark : the national magazine of entertainment ; vanaf 13(1980-1981) 12 : the magazine of entertainment. (New York : Danad Publishing Company vanaf 13(1980-1981) 1 After Dark Magazine Inc., 1974)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijksRedactie : 10 Columbus Circle, New York, NY 10019 ; vanaf 12(1979-1980) 3 : 1180 Avenue of the Americas, NY 10036 ; vanaf 13(1980-1981) 1 : 161 West 54th Street, NY 10019
Engels
Periodiek